Effects of cadmium, lead, zinc and copper on chlorophyll and protein content of rice (Oryza sativa L.) (Chittagong University Journal of Biological Sciences, 2025)
This study investigated the effects of cadmium (Cd), lead (Pb), zinc (Zn), and copper (Cu) on some biochemical constituents like chlorophyll, nitrogen and protein levels in rice. A pot experiment was conducted using agricultural loamy soil amended with graded concentrations of Cd, Pb, Zn, and Cu salts, with untreated soil serving as control. Rice leaf samples were collected after 45 days of transplantation in in-situ conditions and analyzed for chlorophyll content. Nitrogen and protein content in rice grains were determined after harvest at ripening. Results revealed significant (p